Acrometastasis of Neuroblastoma to the Great Toe Revealed by MIBG Scan. (May 2017) - Zheng, Kun; Zhuang, Hongming
Abstract : Abstract: A 3-year-old boy with history of neuroblastoma underwent 123 I-MIBG scan. The whole-body images showed relatively normal tracer distribution except for mild activity in the right foot, which was located in the first metatarsal on SPECT/CT images. The subsequent MRI scan of the right foot showed infiltration of the metatarsal of the right first toe. The findings were consistent with solitary acrometastasis of neuroblastoma to the great toe.